Towards real-time 3D ultrasound planning and personalized 3D printing for breast HDR brachytherapy treatment. Issue 3 (March 2015) - Poulin, Eric; Gardi, Lori; Fenster, Aaron; Pouliot, Jean; Beaulieu, Luc
Abstract Two different end-to-end procedures were tested for real-time planning in breast HDR brachytherapy treatment. Both methods are using a 3D ultrasound (3DUS) system and a freehand catheter optimization algorithm. They were found fast and efficient. We demonstrated a proof-of-concept approach for personalized real-time guidance and planning to breast HDR brachytherapy treatments.